Post-War Philosophy in Norway. Problems, Achievements and Dilemmas - Piotrowska, Ewa (Folia Scandinavica Posnaniensia, 2007)
The aim of the paper is to present the main trends within philosophy in Norway. The author also discusses the most important research works carried out at university centres, the goal of which is to analyse Norwegian post-war philosophy. The predominant movement, so called ‘practical philosophy’, deals with ethical, religious, political, social and economic issues. Many Norwegian philosophers are also active as university teachers or researchers at universities in Oslo (e.g. Arne Naess, Hans Skjervheim, Trond Berg Eriksen, Torstein Tollefsen, Anfinn Stigen) and in Bergen (e.g. Gunnar Skirbekk, Nils Gilje, Vigdis Songe-Møller, Knut Erik Tranøy)